Open Problem for General Class of Superordination-Preserving Convex Integral Operator (Masalah Terbuka untuk Kelas Umum Pengoperasi Kamiran Cembung yang Mengawet Superordinasi) - Saibah Siregar; Maslina Darus; Teodor Bulboacă (Penerbit Universiti Kebangsaan Malaysia, 2011)
Let H(U) be the space of analytic functions in the unit disc U. For the integral operator , , , A  [ f ](z) : K H(U)     with K C H(U), we will determine sufficient conditions on certain parameters a ,β ,Y ,8 for sandwich-type theorem. We will also give some particular cases of the main result obtained for appropriate choices of function h , that also generalises classical results of the theory of differential subordination and superordination